A rare case of type II Amyand’s hernia - Jakovljevic , Stefan; Cvetkovic, Aleksandar; Marko Spasic; Stojanovic, Bojan; Petrovic, Marko; Bojan Milosevic (Journal of the Pakistan Medical Association, 2023)
Amyand's hernia represents an inguinal hernia containing an appendix within the hernia sac. This extremely rare condition occurs in approximately 1% of all inguinal hernias. This report describes the case of an 84-year-old male who presented with a right inguinal mass that intraoperatively turned out to be Amyand's hernia type-II with a gangrenous and perforated appendix. An appendectomy and peritoneal lavage were performed, followed by a hernioplasty where a modified Bassini repair was used. The patient fully recovered, and was discharged from the hospital on the fourth day. A non-reducible inguinal hernia containing a perforated appendix is a very rare emergency that requires immediate intervention to prevent abdominal sepsis. Therefore, while examining an inguinal hernia, the possibility of Amyand's hernia should always be considered. Keywords: Amyand's hernia, Acute appendicitis, Inguinal hernia.